Analisis Undang-Undang Cipta Kerja sebagai Alat Rekayasa Sosial Perlindungan Hak Pekerja Perempuan - Widya Sari Nurcahyanti; Catharina Dewi Wulansari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Female workers play a strategic role across various industrial sectors in Indonesia and significantly contribute to productivity and corporate development. Nevertheless, they remain vulnerable to discrimination and criminal acts due to biological, social, and structural factors that persist within society and the workplace. Previous labor regulations revealed substantial gaps in protecting female workers, particularly regarding night work, sexual violence, and reproductive health rights. The Job Creation Law (Undang-Undang Cipta Kerja/UUCK) was enacted to address these deficiencies and to strengthen legal protection for female workers. This study aims to examine the effectiveness of the UUCK in safeguarding female workers from discrimination and violence, as well as its capacity to shape a corporate culture that upholds workers’ rights. The research employs an interdisciplinary approach that integrates legal studies and sociology to provide a comprehensive analysis. It is analytical in nature and applies a normative legal research method based on a literature review. The data used are secondary data, consisting of primary legal materials such as the 1945 Constitution and labor-related laws, secondary materials including scholarly writings and scientific journals, and tertiary materials such as legal dictionaries and online sources. The analysis is conducted through statutory, conceptual, and comparative approaches. The findings indicate that, despite regulatory improvements, workplace sexual violence remains largely underreported due to stigma and inadequate protection mechanisms. Therefore, the study emphasizes the need to incorporate empirical data and female workers’ perspectives in evaluating the UUCK as a tool of social engineering to create a safe, fair, and equitable working environment.